Active interfacial dynamic transport of fluid in a network of fibrous connective tissues throughout the whole body - Li, Hongyi (Cell Prolif, 2020)
Fluid in interstitial spaces accounts for ~20% of an adult body weight and flows diffusively for a short range. Does it circulate around the body like vascular circulations? This bold conjecture has been debated for decades. As a conventional physiological concept, interstitial space is a micron‐sized space between cells and vasculature. Fluid in interstitial spaces is thought to be entrapped within interstitial matrix. However, our serial data have further defined a second space in interstitium that is a nanosized interfacial transport zone on a solid surface. Within this fine space, fluid along a solid fibre can be transported under a driving power and identically, interstitial fluid transport can be visualized by tracking the oriented fibres. Since 2006, our data from volunteers and cadavers have revealed a long‐distance extravascular pathway for interstitial fluid flow, comprising at least four types of anatomic distributions. The framework of each extravascular pathway contains the longitudinally assembled and oriented fibres, working as a fibrorail for fluid flow. Interestingly, our data showed that the movement of fluid in a fibrous pathway is in response to a dynamic driving source and named as dynamotaxis. By analysis of previous studies and our experimental results, a hypothesis of interstitial fluid circulatory system is proposed.